KINERJA DINAS PERTANIAN DAN PETERNAKAN DALAM UPAYA PENINGKATAN PRODUKTIVITAS PETANI DI KABUPATEN ACEH BARAT - Najamuddin Najamuddin (Universitas Teuku Umar, 2018)
Performance apparaisal are one of important phase for an organization because the result reflect asan aacoomplish measurement reaching tree mission. This research used desrciptive method with qualitative. The research result shown that Performanceof Agricultur and Farm Departement of West Aceh Region has well run and need improvement as consist in the vision and mission that implemented on programs and event at each division in Agriculture and Fam Departemen of West Aceh Region. So as to improve Agriculture and Fam Departemen of West Aceh Region performance continously need cooperation well between manager and staf. A good cooperation between program cast and farmer parties became the objective program in order to improve farmer productivity toward society welfare. Keywords:, Farmers, Performance, Productivity Improvement